2019
DOI: 10.1007/s10578-019-00942-0
|View full text |Cite
|
Sign up to set email alerts
|

How Do Mothers’ Parental Attributions Affect Child Outcomes from a Positive Parenting Intervention? A Mediation Study

Abstract: Problematic parental attributions refer to negative causal explanations for child problem behaviour and are known to predict parenting intervention outcomes. This study examines alternative accounts of how mothers' problematic parental attributions, operationalised as negative pre-treatment and change resistant parental attributions during treatment, may affect child behaviour outcomes from a parenting intervention program. Putative mediators included parental feelings about the child and use of harsh discipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…hostile intent; emphasizing causes that are stable and internal to the child) that interfere with parenting and treatment (Sawrikar & Dadds, 2018). In line with the prediction that attributional change is implicated in the broader change processes of treatment, we found that improvements in mothers' attributions explained unique variance in the outcomes of children with CPs 3 months following treatment (Sawrikar, Hawes, Moul, & Dadds, 2019).…”
Section: From Participation To Enactmentsupporting
confidence: 82%
“…hostile intent; emphasizing causes that are stable and internal to the child) that interfere with parenting and treatment (Sawrikar & Dadds, 2018). In line with the prediction that attributional change is implicated in the broader change processes of treatment, we found that improvements in mothers' attributions explained unique variance in the outcomes of children with CPs 3 months following treatment (Sawrikar, Hawes, Moul, & Dadds, 2019).…”
Section: From Participation To Enactmentsupporting
confidence: 82%
“…Positively worded items were reverse scored and all items were used to calculate a higher-order Total Scale of child-responsible attributions for problem behaviours (e.g., under the child's control, permanent, and dispositional) similar to other self-report measures of parental attributions [35]. The PAM previously showed excellent reliability in clinical samples involving parents of children with behavioural problems [36,37]. The internal consistency for the total scale in the current community sample was acceptable (α = 0.66).…”
Section: Methodsmentioning
confidence: 99%
“…Test-retest reliability calculation based on n = 19 mothers who participated in the survey at two timepoints with approximately eight weeks between administrations (range = 6.82-12.68 weeks). Details of data collection for calculating test-retest reliability are reported in[37] …”
mentioning
confidence: 99%
“…Precisely, parents tend to attribute their children's academic positive outcomes to internal, stable and dispositional factors to the child (ability), whereas they make references to unstable, external and situational factors for the child's negative outcomes (Dunton, McDevitt, & Hess, 1988;Goodnow, 1988;Holloway & Hess, 1985;Natale et al, 2009;Raty, Vanska, Kasanen, & Karkkainen, 2002;Rytkönen et al, 2005). Such an attributional pattern sustains the good caretaker parental role (Sawrikar & Dadds, 2018;Sawrikar et al, 2019). However, some studies have obtained different results.…”
Section: Parental Attributionsmentioning
confidence: 82%
“…Weiner's (1992,2000,2001,2003,2010) attribution theory, on which this study is based, represents a comprehensive theoretical framework for understanding motivation for achievement outcomes from the intrapersonal perspective, which refers to the attributions individuals make for their performance, and from the interpersonal perspective, which concerns the attributions made for outcomes experienced by others, and how perceptions of another's responsibility for an outcome contributes to other-directed emotions (gratitude, anger) and behaviors (punishment, support) (Schunk & Zimmerman, 2006;Wand & Hall, 2018). This theory has proved useful in examining how parents explain and evaluate their children's academic performance (Kinlaw, Kurtz-Costes, & Goldman-Fraser, 2001;Natale et al, 2009;Rytkönen, Aunola, & Nurmi, 2005;Sawrikar, Hawes, Moul, & Dadds, 2019).…”
Section: Parental Attributionsmentioning
confidence: 99%